FBMC and UFMC Multi-Waveform Design for 6G Wireless Networks - Zhraa Zuheir Yahya; Dia M. Ali; Younis Abbosh (Diyala Journal of Engineering Sciences)
The upcoming sixth-generation (6G) mobile is designed with several purposes, such as incredible improvements, ultra-fast speed, ultra-low latency, and massive connections within a small area. Bandwidth Efficiency and extensive coverage, besides sub-millisecond synchronization using a new sub-terahertz spectrum, are also considered. In order to maintain frame consistency, adapt to diverse applications, enable scalability, and minimize interferences, in 6G networks, a multi-waveform architecture is required instead of the individual waveform, which cannot meet the requirements. In this paper, a new approach to the waveform framework is presented. The proposed method integrates multi waveforms, referred to as (Waveforms Interfering). This approach combines two multicarrier schemes within a single frame, and then their performances are independently and collectively checked. The suggested approach has a Power Spectral Density (PSD) with minimal out-of-band radiation (OOBR) and a reduced guard band to 6 subcarriers between the two waveforms without causing interference. The Bit Error Rates (BER) performance compared among different orders of Quadrature Amplitude Modulation (QAM). The minimum BER achieved at 20dB SNR is 9e-7. This comparison reveals diverse performance outcomes based on the modulation orders used. The Peak Average Power Ratio (PAPR) behaves similarly to an individual scheme. This approach can effectively satisfy the strict performance requirements of 6G networks.